1963
DOI: 10.1161/01.res.12.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity of Body Tissues at Low Frequencies

Abstract: The resistivity of tissues of the thorax of dogs has been measured in situ under nearly normal conditions. Additional data have been obtained from humans. Approximate values of tissue resistivity found are 160 ohm-cm for blood, 2,000 ohm-cm for lung, 2,500 ohm-cm for fat, 700 ohm-cm for liver, 250 and 550 ohm-cm (anisotropic) for heart muscle and 150 and 2,500 ohm-cm (anisotropic) for skeletal muscle. Reasons for the differences between these and previously reported values have been found, and in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
1
4

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(185 citation statements)
references
References 13 publications
9
171
1
4
Order By: Relevance
“…The anatomical anisotropy produces an electrical anisotropy (Rush, 1963;Clerc, 1976). Since myocardial cells are depolarized by local circuit currents which are affected by the tissue resistivity (Fozzard, 1979), the velocity of depolarization is anisotropic (Clerc, 1976;Roberts et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anatomical anisotropy produces an electrical anisotropy (Rush, 1963;Clerc, 1976). Since myocardial cells are depolarized by local circuit currents which are affected by the tissue resistivity (Fozzard, 1979), the velocity of depolarization is anisotropic (Clerc, 1976;Roberts et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the anisotropy of gross tissue resistivity (Rush, 1963) and of conduction velocity, it is not surprising that the extracellular voltage drop across a propagating depolarization wave depends on the direction of propagation. We have found that the extracellular voltage across a longitudinal wave is 1.75 ± 0.12 times as great as the voltage across a transverse wave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 the effect of changing the interelectrode distance from 0.05 cm, used in our experiments (GIELEN et al, 1984), to a value of the same order of magnitude as the interelectrode distance mentioned by RUSH et al (1963) (> 0'5cm) is illustrated. The values are calculated for a situation comparable with the four-electrode method, but with infinite large current electrodes.…”
Section: Numerical Resultsmentioning
confidence: 83%
“…When HF current was applied to human tissue, BI decreased because HF current flew in the inner cell. In other words, ECF was determined from BI measured by applying LF current, total body water (TBW) was measured by applying HF current, and ICF was estimated by subtracting the HF impedance value from the LF impedance value [18,19].…”
Section: Studies On Bia Have Been Carried Out By Many Researchers Tomentioning
confidence: 99%